Intermittent hypoxic training for 6 weeks in 3000 m hypobaric hypoxia conditions enhances exercise economy and aerobic exercise performance in moderately trained swimmers - Park, Hun-Young; Shin, Chulho; Lim, Kiwon (Biology of Sport, 2018)
Athletic endurance performance at sea level can be improved via intermittent hypoxic training (IHT). However, the efficacy of IHT for enhancement of aerobic exercise performance at sea level is controversial because of methodological differences. Therefore, the aim of the study was to determine whether the IHT regimen ameliorates exercise economy and aerobic exercise performance in moderately trained swimmers. A total of 20 moderately trained swimmers were equally assigned to the control group (n=10) training in normoxic conditions and the IHT group (n=10) training at a simulated altitude of 3000 m. They were evaluated for metabolic parameters and skeletal muscle oxygenation during 30 min submaximal exercise on a bicycle, and aerobic exercise performance before and after 6 weeks of training composed of aerobic continuous exercise set at 80% maximal heart rate (HRmax) during 30 min and anaerobic interval exercise set at the exercise load with 90% HRmax measured in pre-test during 30 min (10 times 2 min exercise and 1 min rest). According to the results, the IHT group demonstrated greater improvement in exercise economy due to decreases in VO2 (p=.016) and HHb (p=.002) and increases in O 2 Hb(p<.001) and TOI (p=.006). VCO 2 was decreased in the IHT group (p=.010) and blood lactate level was decreased in the control (p=.005) and IHT groups (p=.001). All aerobic exercise performance including VO 2max (p=.001) and the 400 m time trial (p<.001) were increased in the IHT group. The present findings indicate that the 6 week IHT regime composed of high-intensity aerobic continuous exercise and anaerobic interval exercise can be considered an effective altitude/hypoxic training method for improvement of exercise economy and aerobic exercise performance in moderately trained swimmers.